A polymorphism in porcine miR-22 is associated with pork color - Wang, Han; Shen, Zhonghao; Huang, Ruihua; Zhao, Ayong; Jiang, Jiani; Li, Pinghua; Zhou, Xiaolong; Yang, Songbai; Hou, Liming (Frontiers in Veterinary Science, 2022)
MicroRNAs (miRNAs) are post-transcriptional regulators that play key roles in meat colour regulation. Changes in miRNA expression affect their target mRNAs, leading to multifunctional effects on biological processes and phenotypes. In the present study, a G > A mutation site located upstream of the precursor miR-22 sequence in Suhuai pigs was significantly correlated with the meat colour parameter a*(redness) of the porcine longissimus dorsi (LD) muscle. AA genotype individuals had the highest average meat colour a* value, and the lowest miR-22 level. When G>A mutation was performed in the miR-22 overexpression vector, miR-22 expression significantly decreased. Considering that Ca2+ homeostasis is closely related to pig meat colour. Our results further demonstrate that ELOVL6 is a direct target of miR-22 in pigs. The effects of miR-22 on skeletal muscle intracellular Ca2+ were partially caused by the suppression of ELOVL6 expression.